Impact of China's new-type urbanization on energy intensity: A city-level analysis - Lin, Boqiang; Zhu, Junpeng (Energy economics, 2021)
The new-type urbanization strategy proposed by the Chinese government is human-centered urbanization, which emphasizes the coordination of population, economy, society, and ecological environment. Despite extensive research on the impact of traditional urbanization, the impact of the new-type urbanization on energy efficiency is largely unknown. Based on the sample of 193 Chinese cities, this paper investigates the conditional convergence characteristics of energy intensity and explores the role of new-type urbanization on energy saving as well as its transmission channels. The results confirm the existence of condition β-convergence for energy intensity, and the new-type urbanization has a significant energy-saving effect with the effect being greater in resource-rich areas. Moreover, the mechanism analysis shows that the economic agglomeration effect, industrial structure effect, and technological progress effect are important transmission channels through which the new-type urbanization affects energy intensity. This paper adds new insights to understand the new-type urbanization process. •Impact of the new-type urbanization on energy intensity is analyzed.•The new-type urbanization has a significant energy-saving effect.•Regional heterogeneity is found among different types of cities.•Three important transmission channels are identified.